2014
DOI: 10.1093/hmg/ddu052
|View full text |Cite
|
Sign up to set email alerts
|

Defects in pancreatic development and glucose metabolism in SMN-depleted mice independent of canonical spinal muscular atrophy neuromuscular pathology

Abstract: Spinal muscular atrophy (SMA) is characterized by motor neuron loss, caused by mutations or deletions in the ubiquitously expressed survival motor neuron 1 (SMN1) gene. We recently identified a novel role for Smn protein in glucose metabolism and pancreatic development in both an intermediate SMA mouse model (Smn2B/−) and type I SMA patients. In the present study, we sought to determine if the observed metabolic and pancreatic defects are SMA-dependent. We employed a line of heterozygous Smn-depleted mice (Smn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 60 publications
5
58
0
Order By: Relevance
“…The single most important pathological finding for SMA is the loss of lower motor neurons, and denervation at the NMJ is the earliest pathological change in SMA mice (37)(38)(39)(40)(41). However, reduced SMN expression has also been observed to cause skeletal muscle (13,14,16) and vascular system (19,20,49) defects in SMA mice, and SMN is involved in general cellular functions, including small nuclear ribonucleic protein (snRNP) biogenesis (13,(22)(23)(24) and glucose metabolism (17,18,21). Thus, although delivery to the CNS is primordial for SMA therapy, combined targeting of both the CNS and the periphery has the potential of being the optimal approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single most important pathological finding for SMA is the loss of lower motor neurons, and denervation at the NMJ is the earliest pathological change in SMA mice (37)(38)(39)(40)(41). However, reduced SMN expression has also been observed to cause skeletal muscle (13,14,16) and vascular system (19,20,49) defects in SMA mice, and SMN is involved in general cellular functions, including small nuclear ribonucleic protein (snRNP) biogenesis (13,(22)(23)(24) and glucose metabolism (17,18,21). Thus, although delivery to the CNS is primordial for SMA therapy, combined targeting of both the CNS and the periphery has the potential of being the optimal approach.…”
Section: Discussionmentioning
confidence: 99%
“…ISS-N1-targeted SSOs used to treat presymptomatic severely affected neonatal SMA mice, via systemic or intracerebroventricular administration, extend survival from 10 to >100 d (11,12). Although SSO targeting to the CNS is essential, there is also evidence for a peripheral role for the SMN in SMA (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Neuromuscular defects are the most obvious hallmarks of SMA, but SMN is ubiquitously expressed and numerous studies have suggested nonneuronal requirements for SMN function in heart (57-59), liver (60), muscle vascular system (61), lung, intestine (62), and pancreatic islets (63). Therefore, it was not surprising that endosomal defects were observed in other C. elegans tissues when SMN levels were compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of SMN1 creates SMN deficit, leading to spinal muscular atrophy (SMA), a major genetic disease of children and infants [18, 19]. Aberrant expression and/or localization of SMN have been associated with several other diseases, including amyotrophic lateral sclerosis (ALS), metabolic disorders, male infertility, and stress-associated disorders [14, 2022]. Correction of SMN2 exon 7 splicing has proven to confer therapeutic benefits in mouse models of SMA [23, 24].…”
Section: Introductionmentioning
confidence: 99%